Understanding the role of agricultural data on market power in the emerging Digital Agriculture sector: a critical analysis of the BayerMonsanto decision - Atik, Can (ASCOLA Competition Law series, 2021)
This timely book addresses the contemporary complexities within competition law, questioning whether the founding principles of competition law still hold true today. It explores three main present-day challenges for competition law: the impact of the digital economy and innovative sectors, the challenges facing emerging countries, and current institutional issues.